Values-Based Practice in EBLIP: A Review - Bell, Emilia C. (Evidence Based Library and Information Practice, 2022)
Objective – This narrative literature review examines how values and a values-based practice framework are positioned as significant to evidence based practice in libraries. This includes examining the partnership between values and evidence in decision making and reflective practice. The review responds to a gap in the literature on the origins and application of values-based practice in evidence based library and information practice (EBLIP).Methods – Searches for this narrative review were conducted in library and information science databases, discovery tools, and individual journals. Forward and backward citation searches were also undertaken. Searches aimed to encompass both the EBLIP and library assessment literature. Research and professional publications were considered for inclusion based on their engagement with values and values-based practice in EBLIP processes and decisions.Results – The findings highlight how values reflect positionality, driving action and decision making in all stages of evidence based practice in libraries. The literature emphasizes the role of values when practitioners engage with critical reflective practice or invite user voices in evidence. An explicit values-based practice approach was evident in the library assessment literature, though not explicitly addressed in the EBLIP literature or EBLIP models. This is despite a partnership between evidence based practice and values-based practice in the health sciences literature, with literature on person-centred approaches aiming to relate evidence to individuals.Conclusions – The EBLIP literature could further examine how values reflect positionality and drive action and decision making across all stages of evidence based practice. Values-based practice offers an opportunity to critically reflect on whose voices, perspectives, and values are reflected in and contribute to the library and information science evidence base.